The body from the perspective of schools of anthropology - عەبدوڵڵا, ئاسۆ ئیبراهیم; Abdul, Hemn Baqi (Sulaimani Journal for Humanities, 2019)
This research work is an attempt to study general lines of body reading in anthropology school in the last century (1884-1984). This works by focusing on describing and comparing methods.also aims at discovering viewpoints of anthropology schools on body and comparing it to one another. The researcher has tried to present the main directions in which they have studied body and discussed as anthropology phenomena and then he has compared them to one another. In sum, the researcher has reached the point that anthropology doesn't look at the body and its movement as a single aspect of biology, but rather it considers it as an anthropology phenomenon that is strongly combined to culture. Each culture builds its own body and body movement structure. Thus, body is part of culture phenomena and is directly linked to culture developments. The researcher has also reached the point that there are different ideas on culture from anthropology schools, while in nature and criminal anthropology human being are considered as a result of social and cultural developments. They think that building the body of human being is just a mimicked body of the society. The cultural orders also play a great role in creating and building the body. Regarding the religious anthropology, it is thought that religion plays a great role in formalizing the body and controlling its movement.